1992
DOI: 10.2337/diacare.15.11.1527
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Scanning With 111In Is Superior to Magnetic Resonance Imaging in Diagnosis of Clinically Unsuspected Osteomyelitis in Diabetic Foot Ulcers

Abstract: Leukocyte scanning is superior to MRI in detecting clinically unsuspected osteomyelitis in diabetic foot ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…False positive results have been reported in several conditions, including rapidly progressive neuroarthropathy. Due to the poor spatial resolution in indium-111 leukocyte studies, uptake in soft tissues could be incorrectly attributed to bone uptake and vice versa [15,21] . Bone imaging combined with labeled leukocyte imaging improves the diagnostic accuracy of foot osteomyelitis and its differentiation from the soft-tissue infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…False positive results have been reported in several conditions, including rapidly progressive neuroarthropathy. Due to the poor spatial resolution in indium-111 leukocyte studies, uptake in soft tissues could be incorrectly attributed to bone uptake and vice versa [15,21] . Bone imaging combined with labeled leukocyte imaging improves the diagnostic accuracy of foot osteomyelitis and its differentiation from the soft-tissue infection.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological fi ndings are not reliable in establishing the diagnosis in patients with violated bone which will give nonspecifi c fi ndings, being diagnostic in only 3-5% of culture-positive cases. Conventional radiographs have proved to be neither sensitive nor specifi c for the diagnosis of osteomyelitis [13,15,16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that triple-phase 99 Tc-MDP (methylenediphosphonate) scans are of little value in differentiating these entities [36][37][38][39][40][41]. Although bone scanning is sensitive, especially for early infection, it is rather nonspecific, and so unsuitable for distinguishing between neuroosteoarthropathy and infection.…”
Section: Isotope Scanningmentioning
confidence: 99%
“…MRI has the obvious advantages of providing excellent anatomic detail and resolution of both bones and soft tissues. Labeled leukocyte imaging may be more sensitive for detecting clinically unsuspected pedal osteomyelitis and is useful for monitoring response to medical therapy, and evaluating the neuropathic joint (Newman et al, 1991;Newman et al, 1992;Palestro et al, 1998;Palestro and Tomas, 2000).…”
Section: Diabetic Foot Infectionsmentioning
confidence: 99%